Sosialisasi Pencatatan Keuangan dan Perpajakan Pada 13ML Kopi - Rajagukguk, Ronald Hasudungan; Sitanggang, Tina Novianti; Riadi, Riadi; P, Jhon Lismart Benget; Sinaga, Annisa Nauli (Sekolah Tinggi Ilmu Manajemen Sukma Medan, 2025)
Financial management and tax compliance represent the primary challenges faced by micro-enterprises such as Cafe 13ML Kopi in Medan. The core issues identified include the commingling of personal and business finances, as well as the absence of formal financial statements, which hinders business performance analysis and access to financing. This community service activity aims to enhance financial literacy and tax awareness through socialization and technical assistance. The methods employed include motivational lectures, tutorials on preparing financial statements based on simplified standards, and interactive discussions regarding MSME tax issues. The results of the activity indicate an improvement in the partner's understanding of basic accounting equations and the accounting cycle, ranging from transaction recording to the preparation of income statements. Furthermore, the partner now possesses stronger motivation to separate personal and business assets and to report taxes regularly in accordance with the latest regulations. The conclusion of this activity is that basic accounting and tax education can strengthen the internal governance of MSMEs, ultimately supporting business sustainability and management professionalism at Cafe 13ML Kopi.